TRANSFORMASI KEUANGAN SYARIAH DIGITAL DAN TANTANGAN TATA KELOLA SYARIAH : SEBUAH CRITICAL LITERATURE REVIEW - Liza Ulfiana; Sa’idi Sa’idi; Shofyan Hadi; Nurhayanti Nurhayanti; Veni Sofia; Devfy Kartikasari (ISTISMAR, 2026)
Digital transformation has driven fundamental changes in the Islamic finance industry through the adoption of technologies such as financial technology (fintech), artificial intelligence, blockchain, and smart contracts. these developments present both opportunities and challenges for the implementation of Sharia governance. This study aims to analyze the evolution of digital Islamic finance and identify Sharia governance challenges using a critical literature review approach. The research data consists of scholarly literature sourced from reputable journals, academic books conference proceeedings, and relevant official documents. Analysis was conducted using qualitative content analysis, involving a critical synthesis of findings from prior research. The results indicate that digitalization enhances operational challenges regarding regulatory gaps, the validity of digital contracts, algorithmic transpaency, cybersecurity, and the limited competencies of Sharia Supervisory Boards. The importance of developing on "Adaptive Sharia Governance" model that integrates Sharia principles with technology-driven governance to ensure Sharia compliance while supporting the sustainability of the digital Islamic finance industry. Keywords : Transformation, Digital Sharia Finance, Sharia governance